Paraísos ‘barrosos’: el éxtasis como foco central de la poética de Néstor Perlongher (Altre Modernità, 2012)
The last period of Perlongher’s poetry has been considered with some ‘concern’ by criticswho have read the poet's interest in mysticism (especially the cult of the Santo Daime) as a consequence of the abrupt change in his life due to the discovery of seropositivity and, therefore, the impossibility of continuing with sexuality as an instrument of liberation and transcendence. Consequently his latter production (Aguas Aereas, El chorreo de las iluminaciones, El Auto Sacramental) has been considered in the line of ‘discontinuity’.In this essay, on the contrary, I propose a reading of Perlongher’s mystical production based on the idea of continuity with his previous works to show how this perspective can help the critics to focus more clearly the core of his poetical experience.